Endophytic filamentous fungi from a Catharanthus roseus: Identification and its hydrolytic enzymes - Ayob, F.W.; Simarani, K. (Elsevier, 2016)
This paper reported on the various filamentous fungi strains that were isolated from a wild grown Catharanthus roseus. Based on the morphological characteristics and molecular technique through a Polymerase Chain Reaction and DNA sequencing method using internal transcribed spacer (ITS), these fungi had been identified as a Colletotrichum sp., Macrophomina phaseolina, Nigrospora sphaerica and Fusarium solani. The ultrastructures of spores and hyphae were observed under a Scanning Electron Microscope. The hydrolytic enzyme test showed that all strains were positive in secreting cellulase. Colletotrichum sp. and F. solani strains also gave a positive result for amylase while only F. solani was capable to secrete protease. These fungi were putatively classified as endophytic fungi since they produced extracellular enzymes that allow them to penetrate plant cell walls and colonize with symbiotic properties.